Comparative Analysis of Performance in the High-Bar vs. Low-Bar Squat - Manuel González; Archit Navandar; José M. González-Ravé; Roberto Ojeda; Fernando González-Mohíno; Daniel Juárez Santos-García (Applied Sciences)
The objective of this study was to compare the 1 Repetition Maximum (RM) performance in the parallel squat exercise with a low-bar vs. a high-bar technique and to analyze the gender differences. A secondary objective was to analyze the differences in the force–velocity profile between the low- and high-bar squat technique. Nineteen recreational strength-trained participants, 9 men (22 ± 1.9 years, 79.4 ± 13.9 kg, 1.77 ± 0.11 m) and 10 women (27.6 ± 3.12 years, 60.4 ± 5.0 kg, 1.67 ± 0.5 m), participated in this study. All participants performed two evaluations of the 1RM and the force–velocity curve in parallel squat exercises, separated by a week, one with a high bar and the other with a low bar technique. The level of significance set for this study was p < 0.05. The technical × gender interaction was not significant in any of the three variables analyzed: lifted load, mean propulsive velocity, and force. A difference (p < 0.001) in the lifted load and the mean force is observed between the techniques at 1RM, being in both cases (men and women) better in the low-bar performance. A difference (p < 0.001) was observed in relation to the technique × participation interaction when comparing the mean velocity and force obtained with the same absolute submaximal loads in each of the techniques. These data may guide a better and more precise organization of training when performing the squat exercise and differentiating the techniques to be used, using the low bar when the main objective is strength or power training.